Impact on children of a parent with ALS: a case-control study - Calvo, Vincenzo; Bianco, Francesca; Benelli, Enrico; Sambin, Marco; Monsurrò, Maria R.; Femiano, Cinzia; Querin, Giorgia; Sorarù, Gianni; Palmieri, Arianna (Frontiers in Psychology, 2015)
Background: Numerous studies have explored how patients and their caregivers cope with amyotrophic lateral sclerosis (ALS), but the literature completely lacks research on the psychological impact of the disease on patients’ children. The aim of our study was to investigate the emotional and psychological impact of a parent with ALS on school-age children and adolescents in terms of problem behavior, adjustment, and personality characteristics. Methods: The study involved 23 children (mean age = 10.62 years, 6 females) with a parent suffering from ALS, and both their parents. Children were matched for age, gender, and birth-order with a control group of children with healthy parents. They were administered the Youth Self Report (YSR) questionnaire and the Rorschach Comprehensive System, and their healthy parent completed the Child Behavior Checklist (CBCL). Results: Findings clearly showed that, compared with controls, children with a parent who had ALS had several clinically significant adverse emotional and behavioral consequences, with emotional and behavioral problems, internalizing problems, anxiety and depressive symptoms. Children of a parent with ALS scored higher than controls for the Total Problems, Internalizing Problems, Anxious/Depressed and Withdrawn/Depressed scales in the YSR. A relevant percentage of children fell within the clinical range (42.9%) and borderline range (28.6%) for Internalizing Problems. The Rorschach CS confirmed the substantial impact of ALS in a parent on their offspring in terms of internalizing behavior and depression, with adjustment difficulties, psychological pain, and thought problems. Conclusion: Our findings indicate that school-aged children and adolescents with a parent who has ALS are vulnerable and carry a substantially higher risk of internalizing behavior, depressive symptoms, and reactive problems than children with healthy parents. Families affected may need support to cope with such an overwhelming disease.